Pembuatan Bio Oil Dari Sekam Padi dengan Proses Pirolisis Lambat - Nyoto Prasetio; Dhea Pranita; Ari Susandy Sanjaya (Program Studi Kimia, Universitas Lambung Mangkurat, 2020)
Abstract- The pyrolysis of bio oil, and bio char formation of rice husk has been investigated. This research was conducted using the method of slow pyrolysis. Slow pyrolysis process is performed at a temperature of 300oC, 350oC and 400oC with pyrolysis time 90 minutes. These results indicate that the higher temperature, the more yield of bio oil produced, while the yield of char produced decreases. The substances in the bio oil was detected by GCMS (Gas Chromatography-Mass Spectrometry). Key word: slow pyrolysis, bio char, bio oil, rice husk